Hidden familial cardiomyopathies in children: Role of genetic testing. (1st October 2021) - Girolami, F.; Spinelli, V.; Passantino, S.; Bennati, E.; Calabri, G.B.; Olivotto, I.; Favilli, S.
Abstract: Pediatric cardiomyopathies harbour significant phenotypic and genetic heterogeneity. Genetic testing is essential for the initial evaluation and the ongoing care of child and family, although challenges remain regarding its appropriate clinical implementation in minors. We here discuss the key role of genetic diagnosis in the clinical management of two patients. Highlights: Genetics can help to make the diagnosis in hidden Cardiomyopathies and to identify the risk stratification in relatives. Genetics results can influence the clinical treatment, the life style decisions and the prenatal counselling. Genetics can be valuable to optimize chemotherapy and cardioprotective therapy in oncological patients at high risk for DCM.